Global Transcriptome Analysis of Primary Cerebrocortical Cells: Identification of Genes Regulated by Triiodothyronine in Specific Cell Types. - Gil-Ibañez, Pilar; Garcia-Garcia, Francisco; Dopazo, Joaquin; Bernal, Juan; Morte, Beatriz (Cereb Cortex, 2017)
Thyroid hormones, thyroxine, and triiodothyronine (T3) are crucial for cerebral cortex development acting through regulation of gene expression. To define the transcriptional program under T3 regulation, we have performed RNA-Seq of T3-treated and untreated primary mouse cerebrocortical cells. The expression of 1145 genes or 7.7% of expressed genes was changed upon T3 addition, of which 371 responded to T3 in the presence of cycloheximide indicating direct transcriptional regulation. The results were compared with available transcriptomic datasets of defined cellular types. In this way, we could identify targets of T3 within genes enriched in astrocytes and neurons, in specific layers including the subplate, and in specific neurons such as prepronociceptin, cholecystokinin, or cortistatin neurons. The subplate and the prepronociceptin neurons appear as potentially major targets of T3 action. T3 upregulates mostly genes related to cell membrane events, such as G-protein signaling, neurotransmission, and ion transport and downregulates genes involved in nuclear events associated with the M phase of cell cycle, such as chromosome organization and segregation. Remarkably, the transcriptomic changes induced by T3 sustain the transition from fetal to adult patterns of gene expression. The results allow defining in molecular terms the elusive role of thyroid hormones on neocortical development.
Keywords: Animals; Astrocytes; Cells, Cultured; Cerebral Cortex; Fluorescent Antibody Technique; Gene Expression Profiling; Mice, 129 Strain; Mice, Inbred BALB C; Mice, Inbred C57BL; Neurons; Piperazines; Transcriptome; Triiodothyronine

Early transcriptional defense responses in Arabidopsis cell suspension culture under high-light conditions. - González-Pérez, Sergio; Gutiérrez, Jorge; Garcia-Garcia, Francisco; Osuna, Daniel; Dopazo, Joaquin; Lorenzo, Oscar; Revuelta, José L; Arellano, Juan B (Plant Physiol, 2011)
The early transcriptional defense responses and reactive oxygen species (ROS) production in Arabidopsis (Arabidopsis thaliana) cell suspension culture (ACSC), containing functional chloroplasts, were examined at high light (HL). The transcriptional analysis revealed that most of the ROS markers identified among the 449 transcripts with significant differential expression were transcripts specifically up-regulated by singlet oxygen ((1)O(2)). On the contrary, minimal correlation was established with transcripts specifically up-regulated by superoxide radical or hydrogen peroxide. The transcriptional analysis was supported by fluorescence microscopy experiments. The incubation of ACSC with the (1)O(2) sensor green reagent and 2',7'-dichlorofluorescein diacetate showed that the 30-min-HL-treated cultures emitted fluorescence that corresponded with the production of (1)O(2) but not of hydrogen peroxide. Furthermore, the in vivo photodamage of the D1 protein of photosystem II indicated that the photogeneration of (1)O(2) took place within the photosystem II reaction center. Functional enrichment analyses identified transcripts that are key components of the ROS signaling transduction pathway in plants as well as others encoding transcription factors that regulate both ROS scavenging and water deficit stress. A meta-analysis examining the transcriptional profiles of mutants and hormone treatments in Arabidopsis showed a high correlation between ACSC at HL and the fluorescent mutant family of Arabidopsis, a producer of (1)O(2) in plastids. Intriguingly, a high correlation was also observed with ABA deficient1 and more axillary growth4, two mutants with defects in the biosynthesis pathways of two key (apo)carotenoid-derived plant hormones (i.e. abscisic acid and strigolactones, respectively). ACSC has proven to be a valuable system for studying early transcriptional responses to HL stress.
Keywords: Arabidopsis; Blotting, Western; Cell Culture Techniques; Cells, Cultured; Chloroplasts; Cluster Analysis; Gene Expression Profiling; Gene Expression Regulation, Plant; Hydrogen Peroxide; Light; mutation; Oligonucleotide Array Sequence Analysis; Photosystem II Protein Complex; Plant Growth Regulators; Reproducibility of Results; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Signal Transduction; Stress, Physiological; Transcription, Genetic

Hypoxia promotes efficient differentiation of human embryonic stem cells to functional endothelium. - Prado-Lopez, Sonia; Conesa, Ana; Armiñán, Ana; Martínez-Losa, Magdalena; Escobedo-Lucea, Carmen; Gandia, Carolina; Tarazona, Sonia; Melguizo, Dario; Blesa, David; Montaner, David; Sanz-González, Silvia; Sepúlveda, Pilar; et al. (Stem Cells, 2010)
Early development of mammalian embryos occurs in an environment of relative hypoxia. Nevertheless, human embryonic stem cells (hESC), which are derived from the inner cell mass of blastocyst, are routinely cultured under the same atmospheric conditions (21% O(2)) as somatic cells. We hypothesized that O(2) levels modulate gene expression and differentiation potential of hESC, and thus, we performed gene profiling of hESC maintained under normoxic or hypoxic (1% or 5% O(2)) conditions. Our analysis revealed that hypoxia downregulates expression of pluripotency markers in hESC but increases significantly the expression of genes associated with angio- and vasculogenesis including vascular endothelial growth factor and angiopoitein-like proteins. Consequently, we were able to efficiently differentiate hESC to functional endothelial cells (EC) by varying O(2) levels; after 24 hours at 5% O(2), more than 50% of cells were CD34+. Transplantation of resulting endothelial-like cells improved both systolic function and fractional shortening in a rodent model of myocardial infarction. Moreover, analysis of the infarcted zone revealed that transplanted EC reduced the area of fibrous scar tissue by 50%. Thus, use of hypoxic conditions to specify the endothelial lineage suggests a novel strategy for cellular therapies aimed at repair of damaged vasculature in pathologies such as cerebral ischemia and myocardial infarction.
Keywords: Angiopoietin-1; Animals; biomarkers; Cell Culture Techniques; Cell Differentiation; Cell Hypoxia; Cell Transplantation; Cells, Cultured; Down-Regulation; Embryonic Stem Cells; Endothelial Cells; Gene Expression Profiling; Gene Expression Regulation; Humans; Male; Myocardial Infarction; Neovascularization, Physiologic; Oxygen; Pluripotent Stem Cells; Rats; Rats, Nude; Vascular Endothelial Growth Factor A